PCATOOL as a Primary Care Assessment tool: Integrative review (Research, Society and Development, 2022)
Primary Health Care (PHC) is the first level of a humanized and quality health system, which is defined by its fundamental characteristics, such as comprehensiveness, coordination of care, family- and community-centered care, access to first contact and longitudinal age, among other factors. Therefore, the present study aimed to evaluate the performance of Primary Health Care services, according to the use of the Primary care assessment Tool (Pcatool). In terms of methodology, it was an integrative literature review, carried out through bibliographic surveys. Data collection took place in the LILACS, Scielo and Google Scholar databases, from August to September 2022. In the inclusion process, studies were searched between the years 2018 to 2022 in English and Portuguese. Initially, 25 studies were counted, and after discarding, 15 studies remained that served as the basis for this study. In the results, it was evident that the PCATool-Brasil instrument is an important tool created to assess the quality of services in primary health care, according to items that seek to represent the attributes (the characteristics) found in health systems, evidence of high quality, relating those attributes with structural and process aspects in health services.